What is wrong with compliance? - Holm, S. (Journal of medical ethics, 1993)
Non-compliance is a label often used about patients who do not follow therapeutic advice. This paper analyses the notion of compliance, and tries to show that this notion is inextricably bound to a paternalistic conception of the doctor-patient relationship. It is proposed that we should perhaps not talk so much about the non-compliant patient, but instead shift the focus towards the non-compliant doctor.